Factorization!!

When a polynomial f(x) is divided by (x-1),the remainder is 5 and when it is divided by (x-2), the remainder is 7. Find the remainder when it is divided by (x-1)(x-2).

Note by Parmeet Singh
5 years, 1 month ago

No vote yet
3 votes

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

there is a polynomial of degree 2 i.e. a quadratic polynomial

using division algorithm
f(x)= D(x).Q(x) + R(x)

put x-1 =0
x=1

x-2=0
x=2

f(x)=(x-1)(x-2) .Q(x) +R(x)
Let R(x) be Ax+B

now using factor theorem,

f(1)=(0)(-1) + (A+B) = 5
f(2)=(1)(0)+ (2A+B) =7
A+B=5 {1}

2A+B=7 {2}

Sub {1} from {2}

2A+B -A-B =7-5
A=2
B=3

Hence, the remainder is 2x+3

Anshul Agarwal - 5 years, 1 month ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...